Excitation of the 5p57p levels of xenon by electron impact - Sharma, Lalita; Srivastava, Rajesh; Stauffer, Allan D. (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2011)
We have used our relativistic distorted-wave method to calculate cross sections for theelectron-impact excitation of the ground state of xenon to all the5p57p fine-structure levels. The resultsare compared with the recent experimental measurements of Jung et al. [Phys. Rev. A80, 062708 (2009)]. Analytic fits to our cross sections are also providedfor use in plasma modeling studies.
Die 2. 5 in 5p57p im Titel ist hochgestellt
Gesehen am 30.11.2022